Assessment of Pomegranate Juice as Antioxidant in Extender on Cauda Epididymis Spermatozoal Quality of Buck at Refrigerated Temperature - Amarjeet,; Khasatiya, CT; Chaudhary, LM (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present investigation was carried out to study the refrigeration preservation of the cauda epididymal retrieved spermatozoa of buck  in Tris egg yolk citrate (TEYC) dilutor containing pomegranate juice as antioxidant additive. The retrieved cauda epididymal spermatozoa  extended in TEYC dilutor were studied in five groups by adding different concentration of pomegranate juice as additive (0% as control  T1 group and 5%, 10%, 15% and 20% as treatment T2, T3, T4 and T5 groups, respectively) and storing at refrigerated temperature up  to 48 hr. The results showed that the control extender had the least dead, abnormal and HOS non-reacted sperm percent among all  treatments tested and that with increasing the pomegranate juice concentration in dilutor, the percentage of the dead, abnormal and  HOST non-reacted spermatozoa increased significantly. The same trend was observed at all 12 hourly storage intervals indicating its  detrimental effect on epididymal sperms of bucks at refrigeration temperature. The dead, abnormal, and HOST non-reacted sperm  were significantly and positively interrelated with each other (r = 0.53–0.83). It was concluded that the inclusion of pomegranate juice  in TEYC dilutor did not show any beneficial/antioxidant effect on epididymal sperms of buck in fresh or refrigerated semen and in fact  all the levels of pomegranate juice (5% to 20%) were detrimental to cauda epididymal spermatozoa of buck.
Keywords: Buck; Cauda epididymis; Pomegranate juice; Refrigerated temperature; Spermatozoa